Article RETRACTED due to manipulation by the authors The Effect Of Implementing Physical Education Class Management Archery Material To Improve Concentration Elementary School Students - Hendra Setyawan; Suyanto Suyanto; Ngatman Ngatman; Sugeng Purwanto; Suyato Suyato; Arief Darmawan; Abdul Aziz Purnomo Shidiq; Özgür Eken; Ratko Pavlovic; Francesca Latino; Francesco Tafuri; Tiok Wijanarko; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Concentration is needed for students at the stage of physical and psychological growth and development to support successful learning achievement. This research was quantitative research. The research design employed a pre-experimental one-group pretest-post-test design. The research sample was 14 students taken using a purposive sampling method. The concentration data collection technique used a GTC test before and after intervension. The data analysis techniques used were paired sample t-test and n-gain score. The results of the descriptive statistical test show a pretest score of 51.79 and post-test 63.00, meaning there is no increase in the average descriptive score. The results of the paired sample t-test show a significance value of 0.067 > 0.05, meaning there is no significant difference between the pre-test and post-test. The effectiveness test results on applying PE archery material obtain an average value of 0.23, included in the low effectiveness category. The conclusion is that the implementation of descriptive archery material PE class management is able to increase elementary school students' concentration, but there is no significant increase. The implementation of PE material on archery with more specific movement activities will encourage training to focus the mind and eyesight. The research results also provide findings that archery can also be used as a means of PE and physical fitness and as a health therapy to focus the eye's gaze in paying attention to an object to increase concentration power in learning various important things.